Anuson Walter Vella - Renard, Ronald D. (Ronald Duane); Vella, Walter F. (Walter Francis) 1924-1980. Selections (Southeast Asia papers, 1986)
Cremation volume for Vella, Walter F. (Walter Francis), 1924-1980, American author on Thailand; comprises condolences and papers on Thailand by both crematee and others.